Digital Marketing and the Presentation of Corporate Financial Statements: An Analysis of the Literature on Transformation and Impact - Yuliantini, Yuliantini; Saribanon, Euis; Olfebri, Olfebri; Rahmawati, Aisyah; Yulihapsari, Ika Utami (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to analyze the integration of digital marketing with corporate financial reporting, focusing on its impact on transparency, accountability, and the challenges associated with its implementation. The research adopts a qualitative approach through an extensive literature review, systematically examining scholarly articles, industry reports, and case studies from reputable sources. The analysis uses thematic coding to identify trends, challenges, and the implications of integrating digital marketing data into financial reporting. The findings reveal that digital marketing significantly enhances financial transparency and accountability by providing real-time data and facilitating dynamic stakeholder engagement. Platforms such as social media and corporate websites are pivotal in disseminating financial information and receiving real-time feedback, improving financial reports' accuracy. However, integrating digital marketing data poses challenges, including data security, regulatory compliance, and the need for new skills among financial professionals. Companies that effectively harness AI and big data analytics in their financial reporting demonstrate improved forecasting and decision-making capabilities. This integration offers transformative opportunities for businesses to enhance their financial reporting's accuracy and timeliness. Nevertheless, addressing the challenges of data integration and security, as well as bridging the skills gap, is crucial for realizing the full potential of digital marketing in financial reporting.